Her Own Worth: Negotiations of Subjectivity in the Life Narrative of a Female Labourer - Koskinen-Koivisto, Eerika (Studia Fennica Ethnologica, 2014)
"In this study, I examine the life narrative of a female factory labourer, Elsa Koskinen (née Kiikkala, born in 1927). I analyze her account of her experiences related to work, class and gender because I seek to gain a better understanding of how changes in these aspects of life influenced the ways in which she saw her own worth at the time of the interviews and how she constructed her subjectivity. Elsa's life touches upon many of the core aspects of 20th-century social change: changes in women's roles, the entrance of middle- class women into working life, women's increasing participation in the public sphere, feminist movements, upward social mobility, the expansion of the middle class, the growth of welfare and the appearance of new technologies. What kind of trajectory did Elsa take in her life? What are the key narratives of her life? How does her narrative negotiate the shifting cultural ideals of the 20th century? A life story, a retrospective evaluation of a life lived, is one means of constructing continuity and dealing with the changes that have affected one's life, identity and subjectivity. In narrating one's life, the narrator produces many different versions of her/him self in relation to other people and to the world. These dialogic selves and their relations to others may manifest internal contradictions. Contradictions may also occur in relation to other narratives and normative discourses. Both of these levels, subjective meaning making and the negotiation of social ideals and collective norms, are embedded in life narratives. My interest in this study is in the ways in which gender and class intersect with paid labour in the life of an ordinary female factory worker. I approach gender, class and work from both an experiential and a relational perspective, considering the power of social relationships and subject formations that shape individual life at the micro-level. In her narratives Elsa discusses ambivalence related to gendered ideals, social class, and especially the phenomenon of social climbing as well as technological advance. I approach Elsa's life and narratives ethnographically. The research material was acquired in a long-standing interview process and the analysis is based on reflexivity of the dialogic knowledge production and contextualization of Elsa's experiences. In other words I analyze Elsa's narratives in their situational but also socio-cultural and historical contexts. Specific episodes in one's life and other significant events constitute smaller narrative entities, which I call micro-narratives. The analysis of micro-narratives, key dialogues and cultural ideals embedded in the interview dialogues offers perspectives on experiences of social change and the narrator's sense of self"